Find an explicit rule for the nth term of the sequence.

-4, -8, -16, -32, ...

an = -4 • 2n - 1
an = 2 • -4n + 1
an = 2 • -4n
an = -4 • 2n

Respuesta :

Answer:

[tex]a_{n}[/tex] = - 4 × [tex]2^{n-1}[/tex]

Step-by-step explanation:

Note there is a common ratio between consecutive terms in the sequence.

r = - 8 ÷ - 4 = - 16 ÷ - 8 = - 32 ÷ - 16 = 2

This indicates that the sequence is geometric with n th term

[tex]a_{n}[/tex] = a [tex](r)^{n-1}[/tex]

where a is the first term and r the common ratio

Here a = - 4 and r = 2, thus

[tex]a_{n}[/tex] = - 4 [tex](2)^{n-1}[/tex] ← explicit rule